2011
DOI: 10.1007/s10706-011-9462-5
|View full text |Cite
|
Sign up to set email alerts
|

Strength Behavior of Fine Grained Soil Reinforced with Randomly Distributed Polypropylene Fibers

Abstract: Admixtures and reinforcement materials are frequently used in practice to stabilize coarse and fine grained soils and to improve their engineering properties. However, a limited number of studies have been carried out on fiber-reinforced fine grained soils. In this study, a series of unconfined compression tests, direct shear tests, and California Bearing Ratio tests were carried out to investigate the effect of randomly distributed polypropylene fiber on the strength behavior of a fine grained soil. The conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 16 publications
8
21
1
Order By: Relevance
“…The shear failure occurred after a long time from the appearance of the crack. These results similar to the results obtained by the [15,27,28].…”
Section: Results Of Unconfined Compression Testsupporting
confidence: 91%
“…The shear failure occurred after a long time from the appearance of the crack. These results similar to the results obtained by the [15,27,28].…”
Section: Results Of Unconfined Compression Testsupporting
confidence: 91%
“…A number of workers have added fibres to pre-moisture conditioned soils, using hand mixing to ensure sufficient mixing in terms of both distribution and orientation (AlWahab and Al-Qurna, 1995;Li, 2005;Freitag, 1986;Zaimoglu and Yetimoglu, 2011). In all cases the individual fibres clumped and matted to form fibrous balls that had to subsequently be prised apart and redispersed in the soil mass.…”
Section: 2mentioning
confidence: 99%
“…A search of the literature showed that testing has typically been done utilising fibre contents of 0·05-1·25%, with a small number of tests having been conducted using higher contents of around 3-5%, although with difficulty (Al-Wahab and Al-Qurna, 1995;Al-Wahab and Heckel, 1995;Amir-Faryar and Aggour, 2012;Anagnostopoulos et al, 2014;Cai et al, 2006;Chegenizadeh and Nikraz, 2011;Estabragh et al, 2012;Fowmes et al, 2006;Freitag, 1986;Zaimoglu and Yetimoglu, 2011). In the initial compaction tests done in this study, fibre contents of 0·25% and 0·75% were used in order to obtain values at the lower and higher ends of the range.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Continuum approaches involve laboratory tests of or numerical simulations of representative elements of rooted soil, with the strength being represented as a Mohr-Coulomb failure envelope or yield surface, as conventionally used for non-vegetated soil, like fibre-reinforced sands (e.g. Michalowski and Čermák 2003;Zaimoglu and Yetimoglu 2012;Wood et al 2016). This approach is convenient where the dimensions and spacing of the reinforcement are small and behaviour can be homogenised statistically; otherwise, tests are difficult to perform, time consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%